Apakah Pembinaan Intelektual bisa Membuat Warga Binaan Pemasyarakatan dapat Memperbaiki Diri Khususnya di Lapas Kelas IIb Gunungsitoli. - Erwin Romi Satrianus Nazara; Padmono Wibowo (JOURNAL SAINS STUDENT RESEARCH, 2023)
The correctional system is a constructions based system, one of which is intellectual development which aims to realize the goals of correctional. Because intellectual intelligence is closely related to good attitudes and behavior. The research method used is a qualitative method. Intellectual development really needs to be done to prisoners, because with good intellectuals, someone can think abstractly, examine and act effectively and efficiently when carrying out their activities. However, the implementation of intellectual development in prisons in Indonesia is still lacking, which is constrained by several factors such as the lack of direction of guidance, inadequate facilities and also obstacles from the prisoners themselves, so that the intellectual development that has been carried out so far has not had an impact on the realization of the goals penitentiary system.